2014
DOI: 10.3390/soc4030351
|View full text |Cite
|
Sign up to set email alerts
|

Parental Background and Union Formation Behavior of Native Born Individuals in Sweden with a Foreign Background

Abstract: Social cohesion in destination countries is an increasingly important issue due to the multiethnic structures in these countries and due to ongoing international migration. Union formation of individuals across different backgrounds can be seen as an indicator of social cohesion. However, this phenomenon is important not only in the case of first generation migrants but also for their descendants. Thus, this paper analyzes the determinants of intergroup union formation patterns of the native born individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…High endogamy rates among ethnic groups have, for instance, been explained by third party influences (Kalmijn and Van Tubergen, 2010), and, in a qualitative study, the partner’s place of origin and the assumed status of the partner’s family were perceived to be of primary importance in selecting a partner (Haandrikman and Hutter, 2012), suggesting an association between norms and geographical origin. For Sweden, the only relevant studies on recent partner choice focus on migrants, which evidence the importance of parental involvement in partner choice (Çelikaksoy, 2014; Çelikaksoy et al., 2010; Huschek and De Valk, 2012).…”
Section: Preferences Norms and Opportunitiesmentioning
confidence: 99%
“…High endogamy rates among ethnic groups have, for instance, been explained by third party influences (Kalmijn and Van Tubergen, 2010), and, in a qualitative study, the partner’s place of origin and the assumed status of the partner’s family were perceived to be of primary importance in selecting a partner (Haandrikman and Hutter, 2012), suggesting an association between norms and geographical origin. For Sweden, the only relevant studies on recent partner choice focus on migrants, which evidence the importance of parental involvement in partner choice (Çelikaksoy, 2014; Çelikaksoy et al., 2010; Huschek and De Valk, 2012).…”
Section: Preferences Norms and Opportunitiesmentioning
confidence: 99%
“…In fact, studies have shown that there is a positive relationship between education and intermarriage for immigrants or their descendants (see Çelikaksoy 2014Chiswick and Houseworth 2011;Furtado 2012). These studies explain the higher propensity of university graduates to intermarry as follows: mating preference may change as a result of education, universities constitute meeting points for people from different countries and ethnicities, and highly educated people tend to leave areas with a high concentration of immigrants and ethnic minorities.…”
Section: Previous Studies On Intermarriagementioning
confidence: 99%